Resiliensi Remaja Korban Kekerasan Seksual di Kota Langsa - Syahputra, Raju M Akbar; Siregar, Mawardi (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This is a new author's manual and a template for As-Syar’i: Jurnal Bimbingan & Konseling Keluarga. Sexual violence can occur from various circles, including toddlers, children, adolescents and adults. The impact of sexual violence causes various psychological, physical and social problems. Adolescents are more susceptible to sexual violence because of unstable thinking and influencing relationships. One of the provinces that is ranked as prone to sexual harassment is Aceh. According to the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) Aceh recorded cases of sexual violence against women in this region from January to September 2021 reached 697 cases. Even though they have been treated by various parties, there are still victims who feel ashamed, afraid and they often lock themselves in the house, tend to withdraw from their environment, there are also those who are able to be active again in their previous activities, and they consider the traumatic experience to be a traumatic experience. they experienced before is one of life's lessons. The purpose of this study is to see a picture of the resilience of adolescents who are victims of sexual violence. This study took the subject of the category of teenagers who experienced sexual violence. The study used in-depth, semi-structured interviews with coding analysis. The results show that the subject in the process of resilience is influenced by factors, namely social support, finding solutions to problems, self-regulation, strength of character and optimism. The conclusion of the study is that it is able to show the process of resilience and what factors affect resilience in victims of sexual violence. Keywords: resilience, adolescents, sexual harassment.